Campus Canopy, 1949-01-29 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1949)
Simpson To Represent GSWC At Ga. Tech's "Engineer's Day" -- Cup Won By Sophs During SGA Week -- Barter Theater Will Present 'Hamlet' Tonight At 8:00 In GSWC Auditorium -- Four GSWC Students Attend Minimum Foundation Meeting
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals